A comparison of migrant and non-migrant households’ choices on migration and coping mechanisms in the aftermath of cyclone Aila in Bangladesh - Ahmed, Khandaker Jafor; Atiqul Haq, Shah Md; Hyder, Md. Badrul (Frontiers in Environmental Science, 2023)
This research focuses on understanding the complex impact of Cyclone Aila on migration decisions, particularly regarding the motivations that compel specific vulnerable populations to remain in their current locations despite severe consequences. It conducts a comparative analysis of migration choices, adaptive strategies, and adaptive capacities of migrant and non-migrant populations in Bangladesh after the 2009 Cyclone Aila, focusing on the severely affected districts of Satkhira and Khulna. To achieve this, a comprehensive survey of 284 households was conducted, including 130 migrant and 154 non-migrant households. The research utilized statistical techniques, such as frequency distribution, chi-squared tests, and multinomial logistic regression, along with qualitative insights gathered through in-depth interviews and analyzed using NVivo software to provide a more comprehensive understanding of the coping capacities of these households. The findings indicate that the severity of the cyclone experience significantly impacted migration choices, with non-migrant households displaying a firm attachment to their original location because of better economic opportunities, emotional bonds, vibrant social networks, and higher tolerance for adversity. Migrants are attracted to locales, providing better living conditions, safety, and access to healthcare and education. This research also revealed differences in the adaptive strategies adopted by migrants and non-migrants. Migrants have more options for housing, agriculture, livestock management, food security, health and sanitation, and employment. Most migrant households (47.7%) had high adaptive capacities across various domains, such as food security, housing and shelter, crop production, livestock and poultry rearing, health and sanitation, and livelihood prospects. Non-migrant households had much lower percentages of high adaptive capacity, ranging from 5.3 percent to 9.7 percent. These findings suggest that migration can improve adaptive capacity, especially when responding to events, such